Pendidikan Agama Islam dalam Pluralitas Umat Beragama (Studi Kasus di Desa Kedungrejo, Kecamatan Rowokangkung, Kabupaten Lumajang): Islamic Religious Education in the Plurality of Religious Communities (Case Study in Kedungrejo Village, Rowokangkung District, Lumajang Regency) - Subakri, Subakri (LP2M UIN KH.Achmad Siddiq Jember, 2013)
Every religion in this world advocates peace and goodness for humankind. However, every religion also demands a fanatical attitude from its adherents, which gives rise to exclusive followers. This seems paradoxical to the mutual respect among followers of different religions. In this context, religion appears to have two faces: sometimes as a destroyer, yet also as a unifier of humanity. Setiap agama di dunia ini menyerukan kedamaian dan kebaikan bagi umat manusia. Namun, setiap agama juga menuntut sikap fanatik dari para pemeluknya, yang kemudian melahirkan pengikut yang eksklusif. Hal ini seolah menjadi paradoks dengan sikap saling menghormati antar pemeluk agama yang berbeda. Dalam konteks ini, agama seakan memiliki dua wajah: kadang sebagai penghancur, sekaligus pemersatu umat manusia.